The prognostic impact of tumor necrosis in non-muscle invasive bladder cancer - Culpan,Meftun (2022)
SUMMARY OBJECTIVE: We aimed to investigate the impact of tumor necrosis in non-muscle invasive bladder cancer on patients’ recurrence and progression rates and survival outcomes. METHODS: This study was conducted retrospectively in a single tertiary center in Turkey. Medical records of patients who underwent transurethral resection of the bladder tumor between January 2016 and January 2021 were reviewed. Patients with pTa and pT1 non-muscle invasive bladder cancer who had undergone complete resection were included in our study. All pathological specimens were reevaluated for the presence of tumor necrosis. RESULTS: A total of 287 patients (244 males and 43 females) were included in our study. Of them, 33 (11.5%) patients had tumor necrosis. The rates of multiple and large tumors (>3 cm) were higher in patients with tumor necrosis (p=0.002 and p<0.001, respectively). Tumor necrosis was associated with higher rates of pT1 diseases (p<0.001), high-grade tumors (p<0.001), and the presence of lymphovascular invasion (p=0.007). The mean recurrence-free survival of patients with tumor necrosis was 42.3 (4.6) months, and the recurrence-free survival of patients without tumor necrosis was 43.5 (1.8) months (p=0.720). The mean progression-free survival of patients with tumor necrosis was 43.1 (4.6) months, and the progression-free survival of patients without tumor necrosis was 58.4 (0.9) months. In log-rank analysis, there was a statistically significant difference between patients with and without tumor necrosis in terms of progression-free survival (p<0.001). CONCLUSION: In this study, we demonstrated that patients with non-muscle invasive bladder cancer and tumor necrosis in pathological specimens have shorter progression-free survival and more adverse pathological features.